Effect of Different Topical Agents on Remineralization of Early Enamel Lesion– an in vitro Study - Pishevar, Leila; Mazaheri, Romina; Ranjbaran, Fatemehalsadat; Mirzakhani, Mahboobeh; Khodam, Maziar (Journal of Dental School, 2019)
Objective: This study aimed to compare the effect of using Casein phosphopeptide – amorphous calcium phosphate (CPP-ACP) paste, Remin-Pro and Fluoride Varnish on remineralization of enamel lesions. Methods: In this experimental-in vitro study, 60 intact premolars and molars were used and flat enamel surfaces were prepared. The specimens were divided into 6 groups (N=10). After primary DIAGNOdent value measurement and a four-day immersion in demineralizing solution, the DIAGNOdent value were measured. Groups 1, 2 and 3 were treated by Fluoride varnish, CPP-ACP and Remin-Pro respectively, according to the manufacturer instruction and their DIAGNOdent value was read. Groups 4, 5, and 6 were treated by Fluoride varnish, CPP-ACP and Remin-Pro for 1 month (8 hours a day), respectively, and their DIAGNOdent value was measured. Then the specimens of these three groups were demineralized and pH cycled and their DIAGNOdent values were recorded. The data were analyzed by One-way analysis of variance (ANOVA) and repeated measures ANOVA. Results: After a one-month treatment, the DIAGNOdent value significantly decreased in groups 4, 5, and 6 in comparison to the manufacturer instruction (p<0.001). ANOVA test indicated that decrease mean value of DIAGNOdent value was significantly higher for Remin-Pro and CPP-ACP groups than Fluoride varnish group, from entrance time to the study to re-demineralization stage (p<0.001). Conclusion: All the three materials showed a statistically significant amount of remineralization after repeated application but the CPP-ACP and Remin pro were more resistant to redemineralization and pH cycling.